Participation in vocational education and training: a summary of indicators and rates - Regina Dionisius; Nicole Lissek; Friedel Schier (Bundesinstitut für Berufsbildung (BIBB), 2013)
Vocational education and training reporting uses various indicators, rates and guidance values to describe developments and problem areas in VET. There are, however, considerable differences in the construction and significance of some of these indicators, even when they relate to similar facts and circumstances. For this reason, a systematic description of the most important vocational education (and training) seemed apposite in order to facilitate their application. The indicators focus on transitions from the general educational system to the training system (1st threshold"). The present publication explains the calculation method of the individual indicators and documents their scope and explanatory capacity. (Autorenreferat, BIBB-Doku)
urn:nbn:de:0035-0507-9
Keywords: 370